Disseminated Neospora caninum infection in a dog with severe colitis. (November 2020) - Curtis, Benjamin; Harris, Adam; Ullal, Tarini; Schaffer, Paula A.; Muñoz Gutiérrez, Juan
A 12-y-old spayed female Schipperke dog with a previous diagnosis of inflammatory bowel disease was presented with a 2-mo history of severe colitis. The patient's condition progressed to hepatopathy, pneumonia, and dermatitis following management with prednisolone and dexamethasone sodium phosphate. Colonic biopsies identified severe necrosuppurative colitis with free and intracellular parasitic zoites. Postmortem examination confirmed extensive chronic-active ulcerative colitis, severe acute necrotizing hepatitis and splenitis, interstitial pneumonia, ulcerative dermatitis, myelitis (bone marrow), and mild meningoencephalitis with variable numbers of intracellular and extracellular protozoal zoites. PCR on samples of fresh colon was positive for Neospora caninum . Immunohistochemistry identified N. caninum tachyzoites in sections of colon, and a single tissue cyst in sections of brain. Administration of immunosuppressive drugs may have allowed systemic dissemination of Neospora from the intestinal tract.